Assessment of Comorbidities Associated With Allergic Contact Dermatitis in the United States: A Retrospective Claims-Based Study. Issue 6 (18th November 2022) - Hua, Vivian J.; Li, Shufeng; Qian, Mollie F.; Honari, Golara; Sarin, Kavita Y.; Chen, Jennifer K.
Abstract : Background: Allergic contact dermatitis (ACD) is a common dermatologic disease. Patch testing remains the criterion standard for diagnosis. In clinical practice, avoidance may be limited by patient occupation or noncompliance, the pervasive nature of the culprit agent, or barriers to expert care because of socioeconomic, cultural, or geographic factors. Thus, ACD is frequently chronic and/or recurrent; however, the comorbidities associated with ACD are not well characterized. Objective: The aim of the study is to identify associations between ACD and psychiatric, sleep health, cardiovascular, and infectious conditions. Methods: In this study, we used a large US claims database to identify comorbidities associated with ACD diagnosed after patch testing, including psychiatric, sleep health, cardiovascular, and infectious conditions. We also stratified these associations by chronicity of disease. Results: We identified associations between ACD and psychiatric, sleep-related, cardiovascular, and infectious comorbidities. We also found that more chronic ACD was associated with more infectious comorbidities. All of these associations remained significant on further subanalysis when patients with AD and venous stasis were excluded. Conclusions: Allergic contact dermatitis is associated with multiple comorbidities. Further study is required to corroborate these findings, determine causality, and to explore the impact of possible interventions in the workup and management of this common and often debilitating disease.